Pengembangan Media Pembelajaran Fisika Berbasis Macromedia Flash Pro 8 Pada Materi Gelombang Berintegrasi Ayat Al-Quran Kelas XI MIA 4 MAN 1 Durian Tarung Padang - Sari, Milya (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This research is based on the development of science and technology in a more rapid expansion. Educators are required to provide a medium that helps learners find their own learning experience in improving their learning interests, one of the media that is Macromedia Flash Pro 8. This type of research development or Research and Development (R & D) model 4-D models by Thiagarajan and Sammel. Instruments used are questionnaire validity, questionnaire of practicality, and questionnaire effectiveness. The results of research are: (1) generated learning media of physics form of CD based on Macromedia Flash Pro 8 animation on wave material related to verses of Al-Quran in class XI department of MIA. (2) the value of product validity based on the assessment of eleven experts with an average rating of all aspects of 89.96% with very valid category. The value of product practicability according to 2 educators and 31 students of class XI MIA 4 in MAN 1 Durian Tarung Padang very practical with the average value of 86% and 87% respectively. Results of product effectiveness on the interest of learning 31 students with an average value of 86% category is very effective to increase interest in physics learners learners.